Savage vs. Anscombe-Aumann: an experimental investigation of ambiguity frameworks [dataset] - Oechssler, Joerg; Roomets, Alex (Universität, 2020)
The Savage and the Anscombe-Aumann frameworks are the two most popular approaches used when modeling ambiguity. The former is more flexible, but th...
Grant information: Franklin and Marshall College
Gesehen am 29.10.2020
Keywords: Forschungsdaten; Datenbank